Tetraspanins in Extracellular Vesicle Formation and Function - Andreu, Zoraida; Yáñez-Mó, María (Frontiers in Immunology, 2014)
Extracellular vesicles (EVs) represent a novel mechanism of intercellular communication as vehicles for intercellular transfer of functional membrane and cytosolic proteins, lipids, and RNAs. Microvesicles, ectosomes, shedding vesicles, microparticles and exosomes are the most common terms to refer to the different kinds of EVs based on their origin, composition, size and density. Exosomes have an endosomal origin and are released by many different cell types, participating in different physiological and/or pathological processes. Depending on their origin, they can alter the fate of recipient cells according to the information transferred. In the last two decades, EVs have become the focus of many studies because of their putative use as non-invasive biomarkers and their potential in bioengineering and clinical applications. In order to exploit this ability of EVs many aspects of their biology should be deciphered. Here, we review the mechanisms involved in EV biogenesis, assembly, recruitment of selected proteins and genetic material as well as the uptake mechanisms by target cells in an effort to understand EV functions and their utility in clinical applications. In these contexts, the role of proteins from the tetraspanin superfamily, which are among the most abundant membrane proteins of EVs, will be highlighted.